2022
DOI: 10.7759/cureus.21375
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Removal of Retained Surgical Sponge After Caesarean Section: A Case Report

Abstract: Gossypiboma or textiloma denotes the formation of a mass lesion due to the development of foreign body reactions around the retained surgical item in the body. Most of the cases are asymptomatic in the initial postoperative period. Due to the dense adhesions, most of the cases of intra-abdominal gossypiboma are treated by an open approach. Here we present a case of a 38-year-old lady with left iliac fossa pain one month after caesarean section. Contrast-enhanced computed tomography of the abdomen revealed goss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…An RFB can lie dormant in the body for long periods, and the body deals with it in two ways: first, through an exudative, infectious response that leads to abscesses and fistulas, and second, an aseptic fibrinous response that leads to encapsulation and subsequent mass effect [ 5 , 6 ]. A patient with gossypiboma can present with fever, vomiting, obstruction, intra-abdominal sepsis, fistula formation, and gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An RFB can lie dormant in the body for long periods, and the body deals with it in two ways: first, through an exudative, infectious response that leads to abscesses and fistulas, and second, an aseptic fibrinous response that leads to encapsulation and subsequent mass effect [ 5 , 6 ]. A patient with gossypiboma can present with fever, vomiting, obstruction, intra-abdominal sepsis, fistula formation, and gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The two available options for dealing with a gossypiboma are exploratory laparotomy and diagnostic laparoscopy, both followed by the removal of the RFB and needful surgery. While an open method can be quicker and easier and provide better exposure, laparoscopy has advantages, including a less painful postoperative course, smaller scars, early ambulation, early oral intake, lesser risk of hernia, and overall quicker recovery and return to daily life activities [ 5 , 7 ]. However, laparoscopy may involve a longer operating time because of adhesiolysis and the surgical technique and poses a risk of bowel injury during entry to the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…RSI of surgical sponges or gauze are referred to as gossypiboma. This unintentional surgical event is considered a rare occurrence, but the exact incidence is unknown as it is under-reported due to the fear of legal consequences [2]. The operating room is a complex environment with high levels of stress and pressure that accompany technically difficult procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Joint Commission reviews identified RSI as the most frequent sentinel event, surpassing other errors such as wrong patient, wrong site, and/or wrong procedure [3]. RSI should always be removed upon diagnosis given the risk that they represent [2]. Most RSI are detected after clinical discharge when symptoms and signs arise, usually in the weeks after the intervention.…”
Section: Introductionmentioning
confidence: 99%